Management of knowledge, information and organizational changes - Nikolić Miloš; Vesić Tamara; Stošić-Mihajlović Ljiljana (Trendovi u Poslovanju)
In the modern business environment focused on dinamic market and difficult economic conditions, professional life of co-workers is often taken as more important than private life. Organizations expect much more from their employees, especially from managers - to neglect their private life and be exclusively dedicated to organisation and its success. Therefore, the emphasis is laid upon managerial population, which is being increasingly 'torn', facing a dilemma how to answer their work requests, without putting their private life aside. The aim of this work is to show the conception of theoretic questions which have to connect styles of knowledge management with information and organizational changes, life and professional styles of managers, as well as with stressing at work, including definition of considered tasks and their delimitation from similar subjects. Information are becoming a starting point, a ticket for understanding and solving problems in menagment, as well as in considering possibilities for improving or innovation of business. In the conditions of rapid changes in the global market, companies must be flexible and dynamic. This imposes the need for a large number of contacts and transactions with the environment, which in turn implies the existence of large amounts of data and information to be collected and analyzed.